Perceptions Toward the Use of Digital Technology for Enhancing Family Planning Services: Focus Group Discussion With Beneficiaries and Key Informative Interview With Midwives - Yousef, Hind; Al-Sheyab, Nihaya; Al Nsour, Mohannad; Khader, Yousef; Al Kattan, Malika; Bardus, Marco; Alyahya, Mohammad; Taha, Hana; Amiri, Mirwais (Journal of medical Internet research, 2021)
Background: Modern family planning (FP) methods allow married couples to discuss and determine the number of children and years of spacing between them. Despite many significant improvements in FP services in Jordan, there are still many issues related to the uptake of FP services for both host communities and Syrian refugees, due to limitations in the health care system based on public health facilities. Digital technologies can provide opportunities to address the challenges faced in the health system, thus offering the potential to improve both coverage and quality of FP services and practices. Objective: The aim of this study was to explore the perceptions of Jordanian women, Syrian refugees, and midwives in Jordan toward the use of digital health technology to support and enhance access to FP services. Methods: We employed a qualitative study based on semistructured, face-to face key informative interviews with 17 midwives (providers) and focus group discussions with 32 married women of reproductive age (clients). Both midwives and clients were recruited from 9 health centers in 2 major governorates in Jordan (Irbid and Mafraq), where 17 in-depth interviews were conducted with midwives and 4 focus groups were conducted with the women. Each focus group included 4 Syrian refugees and 4 Jordanian women. The transcribed narratives were analyzed using inductive thematic analysis. Results: Three major themes were derived from the narratives analysis, which covered the pros of using digital technology, concerns about digital technology use, and the ideal app or website characteristics. Ten subthemes emerged from these 3 main themes. Overall, midwives and women (Syrian refugees and host communities) agreed that digital technology can be feasible, cost-effective, well accepted, and potentially beneficial in increasing woman’s awareness and knowledge regarding the FP methods and their side effect. Furthermore, digital technology can assist in enabling women’s empowerment, which will allow them to make better decisions regarding FP use. No harmful risks or consequences were perceived to be associated with using digital technology. However, several concerns regarding digital technology use were related to eHealth literacy and the accuracy of the information provided. Midwives were mainly concerned about the patients who would rely mostly on the technology and choose to avoid consulting a health care professional. Conclusions: As perceived by midwives and women, incorporating digital technology in FP services can be feasible, cost-effective, well accepted, and potentially beneficial in increasing woman’s awareness regarding the FP methods and their side effect. It may also empower the women to play an active role in the shared (with their husband and family) decision-making process. Therefore, digital technologies are recommended to address the challenges faced in health system and to improve both the coverage and the quality of FP services and practices.